Psychoanalytic and historical perspectives on the leadership of Donald Trump narcissism and marketing in an age of anxiety and distrust - Maccoby, Michael 1933-; Fuchsman, Ken (Routledge, Taylor & Francis Group, 2020)
"What is Donald Trump's personality? Is he mentally ill? What in American culture and history enabled him to become president? How does his personality shape his policies and leadership? In this fascinating and highly relevant new book, these questions are answered by a selection of expert contributors, including psychoanalysts, historians, and a sociologist. Narcissism is defined and applied to Donald Trump, his personal history and style of leadership, and the relationship between Trump and his base is explored as a symptom of his needs and the needs of his followers. Our culture and our politics are put under the lens, as chapters draw on contemporary academic and journalistic analysis, continuing discussions around gaslighting, demagoguery and fascism in terms of their validity in application to Trump. This book refutes many of the mental health experts that label Trump as suffering from a narcissistic personality disorder and makes the case that Trump's personality combines a marketing and narcissistic orientation that determines his behavior and policies. The authors also assert that to understand Trump's rise and his followers, it is valuable to combine psychoanalytic, historical, and sociological perspectives and the book will therefore be of great interest to academics in those fields and all those with an interest in contemporary American politics"--
Literaturangaben
Keywords: Trump, Donald -- 1946-; Geschichte; Persönlichkeitsstruktur; Anhänger; Erfolgsfaktor; USA; Trump, Donald / 1946- / Public opinion; Presidents / United States / Election / 2016; Personality and politics / United States; Political psychology / United States; Political campaigns / United States; Communication in marketing / United States; Persuasion (Rhetoric); Trump, Donald / 1946-; Communication in marketing; Personality and politics; Political campaigns; Political psychology; Presidents / Election; Public opinion; United States; 2016; Aufsatzsammlung